PENGAKUAN PEMERINTAH KABUPATEN TERHADAP MASYARAKAT HUKUM ADAT DAYAK MERATUS DAN HAK ATAS TANAHNYA DI KECAMATAN LOKSADO KABUPATEN HULU SUNGAI SELATAN KALIMANTAN SELATAN - , Dewi Fahrina Megasari, Sulastriyono, SH., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of this research is to know the Government's recognition of Hulu Sungai Selatan Regency of the indigenous Dayak Meratus community and legal rights over their land in district Loksado of Hulu Sungai Selatan Regency, South Kalimantan. This is a research on Government's recognition on District of the indigenous Dayak Meratus community and legal rights over their land in district Loksado of Hulu Sungai Selatan Regency, South Kalimantan. It is a sociological research, which is a juridical law that sees legal studies as a symptom or social institution. This research was conducted in four villages in the area of the District of Loksado in Hulu Sungai Selatan Regency namely, Hulu Banyu village, Malinau village, Loksado village, and Lok lahung village. The numbers of respondent are eleven (11), while the resource numbers are two (2) people. The selection of samples is carried out by purposive technique and primary data collection through observation and interviewing methods. After the secondary and primary data are collected then analyzed qualitatively. The results showed factors of the reasons of Government Hulu Sungai Selatan Regency has not recognized the Indigenous Dayak Meratus Community and Legal Rights Over their land in district Loksado of Hulu Sungai Selatan Regency is no aspirations of society as a whole of the Indigenous Dayak Meratus Community and no initiative from the Representatives of Local Authorities in making regulations in some areas, DPRD awaiting the presence of aspirations of the community law itself to make the change so that BPN could not follow up it yet, the obstacles faced is the lack of understanding of customary law society on the customary rights and has not been any recognition on the legality of the Government of Hulu Sungai Selatan Regency in the form of Regional Regulations. While the efforts made are only proposed indigenous governance stewardship and structures as well of the indigenous community of Loksado, further attempts from the local authorities are only waiting for the aspiration and the latter the efforts made by NGOS and public against the government conducting advocacy on the rights of indigenous peoples.